(untitled) (Dhaka University Journal of Biological Sciences, 2021)
A pot experiment was conducted in the net house to evaluate the growth and yield response of two vegetables as influenced by the application of maize straw ash in mixed soil. The vegetables were White Malabar Spinach (Basella alba L.) and Red Malabar Spinach (Basella rubra L.). The mixing of acid soil with calcareous soil was done at 3:1 ratio. Maize straw ash was applied at different rates such as T2 (1 ton/ha), T3 (2 ton/ha) and T4 (3 ton/ha). The control as T1 received no amendment. Plant height, base diameter and fresh weight of the Spinach were significantly (p ≤ 0.05) increased from the control treatment. All the studied growth parameters attained significant improvement for the T3 (2 ton/ha) among all treatments in both the varieties of Malabar. Nutrient contents (N, P, K, S, Ca, Mg, Fe, Mn, Zn and Cu) of Red Malabar Spinach increased significantly for ash treatments and the highest increment of the N, P, S, Na, Ca, Mg and Zn were obtained by the T3 treatment. For White Malabar Spinach, all the nutrients were increased significantly for T3 compared to the control, except for the N (insignificant increase) and Ca (decrease). The application of maize straw ash at the rate of 2 ton/ha (T3) increased plant growth, yield and nutrient contents in both the varieties of Malabar which might be attributed that, the maize straw ash can be considered as an amendment for the improvement of crop growth that may also have lasting effect on soil quality as well as economic and eco-friendly. Dhaka Univ. J. Biol. Sci. 30(2): 207-219, 2021 (July)